A Cross Sectional Analysis of Tourism Development and Social Development - AMAN, Tauseef; SHAH, Mussawar; JAMAL, Humera; KHAN, Younas; ARIF, Muhammad; NOOR, Rubina (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.12.2(50).16, 2021)
The major objective of this study was to measure the association between various interventions and Chitral Gole National Park (CGNP) role in preservation of bio-diversity and socio-economic uplift. A sample size of 346 respondents was randomly selected from total population of 3326 from the 4 selected villages on the basis of close proximity. A conceptual framework including dependent variable social development and independent variable tourism development were taken. The data were analyzed through frequency and percentage distribution. Moreover, Chi-square test was applied to know the relationship between dependent and independent variables at bi-variate level. In bi-variate analysis a highly significant (P=0.000) relation was found between CGNP is main source of promoting tourism in Chitral,tourists do any impacts upon local community in terms of increased business activities, local culture is safeguarded despite influx of tourists in the area, tourism produced employment opportunities, and social development. Qualitative data supported the empirical findings, however tourism brings economic opportunities at micro and macro level, but unfortunately CGNP is not as satisfactory regarding generating income since its establishment. The government should ensure to make such polices pertaining to the entrance fee, provides accommodation services on payment to the tourists and to reserve the entrance fee or any other form of taxes to ensure CGNP to spend on self-sustaining basis by ensuring refinement in the procedures as well.